PENGEMBANGAN MATERI PENDIDIKAN AGAMA ISLAM KURIKULUM MERDEKA DI MTS - Tini Melinda Nst; Asmaiwaty Arief; Rehani Rehani (CV. ALIM'SPUBLISHING, 2025)
This study aims to look at the development of Islamic religious education materials and the problems of developing Islamic religious education materials in the independent curriculum at the MTs education unit level, this research sees the importance of a deep understanding of the development of Islamic religious education materials in schools in accordance with the independent curriculum so that learning objectives can be achieved optimally besides that there are also several challenges that hinder the development of Islamic religious education materials in accordance with the independent curriculum, The research method used in this research is library research or library studies where in finding the results of the research the data taken can be found in books and research articles and analyzing the findings, the purpose of this research is to answer problems and become reading material in developing PAI learning materials at the MTS education unit level.